Ruthenium-catalyzed olefinic C–H alkenylation of enol-carbamates: highly stereo-selective synthesis of (Z, Z) and (Z, E)-butadienes. Issue 96 (20th November 2017) - Li, Tingyan; Zhang, Jian; Yu, Chunbing; Lu, Xiunan; Xu, Liqing; Zhong, Guofu
Abstract : Cross-coupling reactions of enol carbamates with alkynes or alkenes are reported, using an inexpensive ruthenium catalyst. Abstract : Cross-coupling reactions of enol carbamates with alkynes or alkenes are reported, using an inexpensive ruthenium catalyst. With the assistance of the directing group OCONMe2, the protocols provide mild, stereo-selective and efficient routes for the preparation of valuable ( Z, Z ) and ( Z, E )-butadiene skeletons.